House Prices and the Credit-Driven Household Demand Channel: The Case of the Irish Economy - David Cronin; Kieran McQuinn (Credit and Capital Markets – Kredit und Kapital, 2021)
The performance of the Irish economy stands out across western economies over the past two decades as the later years of its "Celtic Tiger" phase gave way to a sharp and extremely large economic downturn between 2008 and 2012. This severe recession has been followed by a Lazarus-style economic recovery in recent years. This paper examines the role played by the credit-driven housing net worth channel in the path that Irish economic performance has taken between 2002 and 2019 by specific reference to developments in the domestic labour market. We find a significant positive relationship between housing net worth and employment growth in Ireland, manifesting itself through the non-traded sector of the economy between 2007 and 2012. This followed the emergence and then bursting of a substantial credit-fuelled housing market bubble in the Irish residential property market. Our analysis indicates no evident link between economic activity and a credit-driven housing net worth channel in recent years. This may reflect market and regulatory responses to the banking crisis-led recession of the late 2000s and early 2010s.
Keywords: E24; E32; E44; 330; Household Wealth; House Prices; Employment